Therapeutic efficacy of a galactoglucan from Pleurotus citrinopileatus in constipation: modulation of aquaporin signaling and intestinal barrier - Gao, Yi; Deng, Lan; Chen, Yuanyuan; Qin, Peiyou; Zhao, Yuanyuan; Zhao, Xiaoyan; Liu, Wei; Wang, Dan; Zhao, Shuang (Frontiers in Nutrition, 2025)
IntroductionConstipation is a prevalent gastrointestinal disorder demanding effective therapeutic strategies. This study investigated the therapeutic potential of Pleurotus citrinopileatus polysaccharide (PCP-g), a novel galactoglucan, against sucralfate-induced constipation murine model, focusing on intestinal motility, fecal parameters, aquaporin signaling, and gut microbiota modulation.MethodsPCP-g was purified from P. citrinopileatus and its physicochemical properties were characterized. To evaluate the effects of PCP, the research utilized intestinal motility assays, fecal analysis, and in vitro fermentation. The role of Aquaporin 3 (AQP3) in constipation, especially regarding the PKA - phosphorylation mechanism, was investigated. The influence of PCP-g on PKA, phosphorylated PKA, AQP3, and tight junction proteins were examined at both the mRNA and protein levels.ResultsPCP-g was identified as a homogeneous galactoglucan with a molecular weight of 7.49 × 103 kDa, characterized by a backbone consisting of 1→4-linked glucose (Glcp) and branches of mannose (Manp) and Glcp. The composition of PCP-g includes Glc, Gal, Man, L-Fuc, Rha, GlcA, and Ara, in a molar ratio of 1.00:0.16:0.13:0.01:0.006:0.005:0.006. The oral administration of PCP-g resulted in a significant reduction in constipation symptoms, as indicated by an increase in fecal water content, normalization of pellet formation, enhancement of total fecal mass, decreased latency to the first stool, and improved intestinal propulsion. Furthermore, PCP-g was found to elevate the production of short-chain fatty acids (SCFAs) while simultaneously reducing intestinal gas. Mechanistically, PCP-g suppressed the PKA-dependent phosphorylation of AQP3, leading to the downregulation of AQP3 overexpression and enhanced colonic epithelial permeability. Concurrently, PCP-g reduced the expression of tight junction proteins ZO-1 and Occludin, contributing to the increase in fecal water content.DiscussionPCP-g effectively alleviates constipation by enhancing intestinal motility and fecal hydration. It modulates the PKA-AQP3 signaling pathway to improve colonic water permeability and positively influences the gut environment through the generation of SCFAs. These findings suggest that PCP-g may serve as a promising therapeutic candidate for the treatment of constipation, operating through aquaporin signaling and the regulation of the gut environment. The study advocates for further clinical trials and highlights the potential of edible mushroom polysaccharides in the management of constipation.